Studies on self-association, biological activity and DNA binding properties of a series of water soluble, mixed ligand [Pt(diimine)N,N-dihydroxyethyl-N'-benzoylthioureato]CI complexes - Wu, Yu-Shan (Department of Chemistry, 2014)
Includes bibliographical references.